Pulsating string solution and stability in two parameter χ-deformed background - Rashmi R Nayak; Nibedita Padhi; Manoranjan Samal (Journal of High Energy Physics)
Abstract In this paper, we investigate pulsating string solutions within the context of two parameter χ-deformed R $$ \mathcal{R} $$ × S 2 background. We derive the energy and oscillation number relation for the deformed R $$ \mathcal{R} $$ × S 2 in short string limit. Additionally, we derive the first order perturbation equation for pulsating string in this specific background. As a special case of the two parameter deformed background, we examine the stability of the pulsating string solution in one parameter deformed R $$ \mathcal{R} $$ × S 2 and AdS 3 background by setting one of the deformation parameters to zero.